DAFTAR PERIKSA KUMBANG SUBFAMILI LAMIINAE (COLEOPTERA: CERAMBYCIDAE) DI SULAWESI: BAGIAN I, GUNUNG TAMBUSISI - Fahri, Fahri; Loulembah, Moh. Rizki; Fitrallisan-Fahri, F (Berita Biologi, 2023)
This study aims to provide data on the beetle species of the Subfamily Lamiinae (Cerambycidae) on Mount Tambusisi, Central Sulawesi. Sample collection was carried out from June to July 2022 on Mount Tambusisi in cocoa plantation, agroforestry, secondary forest and primary forest. Sample identification was carried out at the Laboratory of Animal Biosystematics and Evolution, Department of Biology, Faculty of Sciences, Tadulako University. Specimens were preserved dry according to museum standards and kept at the Laboratory of Animal Biosystematics and Evolution, Department of Biology, Tadulako University and at the Museum Zoologicum Bogoriense-MZB (PRBE-BRIN) Cibinong. Specimen are described based on morphological characteristics. A total of 17 species of beetles from the Lamiinae subfamily were collected from Mount Tambusisi such as Acalolepta rusticatrix, A. mattuladaii, A. celebensis, Sternohammus celebensis submaculatus, Granulorsidis sp., Pelargoderus alcanor thomsoni, Epepeotes lugubris, E. plorator celebensis, Olenecamptus bilobus, Trachelophora sp., Gnoma pulverea, Sybra cf. alternans, S. aequabilis. The five morphospecies that have not been identified down to the species level. Several species of cerambycid beetles with a wide distribution in the Oriental region, the Malay Archipelago to Indo-Australia such as Acalolepta rusticatrix, Olenecamptus bilobus, and Pterolophia melanura. While the other 9 species are endemic to Sulawesi.